Colour parameters and shade correspondence of CAD–CAM ceramic systems. Issue 6 (June 2015) - Della Bona, Alvaro; Pecho, Oscar E.; Ghinea, Razvan; Cardona, Juan C.; Pérez, María M.
Highlights: Spectral reflectance, colour parameters and colour differences between CAD–CAM ceramics and the corresponding nominal shade of Vita Classical shade guide were evaluated. Colour differences were compared to the perceptibility and the acceptability thresholds. None of the ceramic systems evaluated were able to properly match the corresponding nominal shade from Vita Classical shade guide. Abstract: Objectives: To evaluate colour differences between (1) CAD–CAM ceramic systems considering shades A1, A2 and A3 and the corresponding nominal shade of VC (Vita Classical shade guide) and (2) shades A1–A2, A2–A3 and A1, A2 and A3 within the same ceramic system. Methods: Samples of shades A1, A2 and A3 were fabricated ( n  = 5) from CAD–CAM ceramic blocks (IPS e.max ® CAD LT and HT, IPS Empress ® CAD LT and HT, Paradigm™ C, and VITABLOCS ® Mark II) and polished to 1.0 ± 0.01 mm in thickness. Spectral reflectance and colour coordinates were measured using a spectroradiometer inside a viewing booth using the CIE D65 illuminant and the d/0° geometry. Spectral reflectance curves were compared using VAF coefficient and were statistically analyzed using Kruskal–Wallis and the Mann–Whitney U test ( α  = 0.05). Colour coordinates were statistically analyzed using one-way ANOVA, Tukey's test with Bonferroni correction ( α  = 0.001). All colour differences ( Δ E ab * and Δ E 00 ) were analyzed through comparisons with the PT – perceptibility and AT – acceptability thresholds for dental ceramics. Results: Δ E between ceramic systems and its corresponding shade ranged from 6.32 to 13.42 ( Δ E ab * ) and 4.48 to 9.30 (Δ E 00 ). Δ E between shades A1–A2, A2–A3 and A1, A2 and A3 ranged, respectively, 1.93–4.82, 1.22–5.59 and 3.63–8.84 ( Δ E ab * ); 1.54–3.87, 1.03–3.90 and 2.95–6.51 (Δ E 00 ). Conclusions: Considering the corresponding nominal shade from VC, none of the ceramic systems showed colour differences below the AT. In addition, some ceramic systems showed colour differences below AT (shades A1–A2 and A2–A3) and below PT (shades A2–A3). Clinical significance: Careful adjustments should be made to the final shade of CAD–CAM ceramic restorations to reach a clinically acceptable shade match.